2008
DOI: 10.1111/j.1574-6968.2008.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of endophytic bacteria fromEucalyptusspecies seeds and colonization of seedlings byPantoea agglomerans

Abstract: The diversity and beneficial characteristics of endophytic microorganisms have been studied in several host plants. However, information regarding naturally occurring seed-associated endophytes and vertical transmission among different life-history stages of hosts is limited. Endophytic bacteria were isolated from seeds and seedlings of 10 Eucalyptus species and two hybrids. The results showed that endophytic bacteria, such as Bacillus, Enterococcus, Paenibacillus and Methylobacterium, are vertically transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
0
27

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(141 citation statements)
references
References 37 publications
6
108
0
27
Order By: Relevance
“…It has been previously isolated from the rhizosphere of maize [38] and wheat [39] and has been also found as an endophyte of Eucalyptus, soybean, and Phaseolus vulgaris beans [31,33,40].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously isolated from the rhizosphere of maize [38] and wheat [39] and has been also found as an endophyte of Eucalyptus, soybean, and Phaseolus vulgaris beans [31,33,40].…”
Section: Discussionmentioning
confidence: 99%
“…Pantoea agglomerans 33.1, isolated from Eucalyptus grandis plants (58), and its derivative tagged strain, 33.1::pNKGFP (25), as well as Escherichia coli derivatives were routinely grown at 28°C and 37°C, respectively, on Luria-Bertani (LB) medium (67). The tagged strain 33.1::pNKBOR was obtained according to the methodology described by Ferreira et al (25). All of the strains (Table 1) were stored in 20% glycerol at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown evidence of the benefits of endophytic microorganisms in eucalyptus plantlets; for instance, they have been shown to increase the rooting indexes and vegetative biomass or act as biocontrol agents in improving plant resistance when challenged with different pathogens (Mafia et al, 2005;Ferreira et al, 2008;Procópio et al, 2009). The present study involved the isolation of endophytic bacteria from eucalyptus and the evaluation of their potential for root and aerial growth promotion in clonal plantlets of Eucalyptus urograndis.…”
Section: Introductionmentioning
confidence: 99%